2007
DOI: 10.1289/ehp.9932
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Toxicokinetics and Toxicodynamics of Paraquat in Mouse Brain

Abstract: BackgroundParaquat (PQ) has been implicated as a risk factor for the Parkinson disease phenotype (PDP) in humans and mice using epidemiologic or experimental approaches. The toxicokinetics (TK) and toxicodynamics (TD) of PQ in the brain are not well understood.ObjectivesThe TK and TD of PQ in brain were measured after single or repeated doses.MethodsBrain regions were analyzed for PQ levels, amount of lipid peroxidation, and functional activity of the 20S proteasome.ResultsParaquat (10 mg/kg, ip) was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 50 publications
(66 reference statements)
3
58
2
Order By: Relevance
“…Although this is the first study to evaluate the role of P-gp in paraquat pharmacokinetics, there have been other studies to measure paraquat pharmacokinetics in chronic studies (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013). The paraquat plasma concentrations we observed following an oral dose in FVB mice were approximately a magnitude less than what has been observed following an intraperitoneal dose to C57BlJ/6 mice; correspondingly, the paraquat brain concentrations we observed were also lower (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Although this is the first study to evaluate the role of P-gp in paraquat pharmacokinetics, there have been other studies to measure paraquat pharmacokinetics in chronic studies (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013). The paraquat plasma concentrations we observed following an oral dose in FVB mice were approximately a magnitude less than what has been observed following an intraperitoneal dose to C57BlJ/6 mice; correspondingly, the paraquat brain concentrations we observed were also lower (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013).…”
Section: Discussioncontrasting
confidence: 52%
“…The paraquat plasma concentrations we observed following an oral dose in FVB mice were approximately a magnitude less than what has been observed following an intraperitoneal dose to C57BlJ/6 mice; correspondingly, the paraquat brain concentrations we observed were also lower (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013). Paraquat has highly variable bioavailability depending upon the route of administration, with the majority of an oral dose found in the feces, which may explain some of the differences in observed plasma concentrations in the different mouse strains (Daniel and Gage, 1966;Chui et al, 1988).…”
Section: Discussioncontrasting
confidence: 50%
“…In addition paraquat showed little penetration into the brain structures of rats with an intact blood-brain barrier [28,29]. More recent studies, however, have reported the ability of paraquat to cross the blood-brain barrier, possibly via the neutral amino acid transporter [30], and to accumulate in certain brain regions of the mouse [31].…”
Section: Paraquatmentioning
confidence: 98%
“…PQ treatment elicits a selective and dose-dependent loss of nigral DA neurons with associated modest decreases in striatal dopamine nerve terminal density and mildly decreased motor behavior (9,64). Following sustained systemic intraperitoneal administration, PQ was found to have a very long half-life in the mouse brain (up to 28 days) and was associated with ongoing lipid peroxidation (77). Moreover, in a chronic rat PQ model, minor decreases in DA neurons and slight increases in DA neurotransmission were observed at 4 weeks; by 24 weeks significant DA neuron loss and DA neurotransmitter depletion were observed, indicating a potentially chronic neurodegenerative process induced by PQ treatment (74).…”
Section: Paraquat and Maneb Models Of Parkinsonismmentioning
confidence: 99%